Teaching health promotion competencies in undergraduate dentistry training: A unique pedagogical approach - Allen, Tammy; O'Loughlin, Mary; Croker, Felicity (Health promotion journal of Australia, 2022)
Issue Addressed: Using appropriate pedagogical approaches in undergraduate dentistry training is important to develop student's health promotion knowledge, and to shape their attitude towards using these competencies in future dentistry practice. This brief report documents the signature pedagogical approach developed for an undergraduate health science subject at James Cook University, to teach dentistry students health promotion competencies. Pedagogical Approach: The signature pedagogy involves three key approaches - experiential learning, cooperative learning and inquiry-based learning. Experiential learning "beyond the classroom" enables students to develop and deliver a school-based oral health promotion program. "Inside the classroom," role-plays encourage students to apply their health promotion skills to real-world dentistry scenarios. Cooperative learning techniques such as "think, pair, share" create a supportive environment for students to confidently exchange ideas; and inquiry-based learning engages students in thinking critically about health promotion strategies to address contemporary oral health challenges. These pedagogical approaches have developed student's understanding of the health promotion competencies required of a newly qualified dentist. Conclusion: Pedagogical approaches that engage dentistry students in experiential, cooperative and inquiry-based learning are important considerations for undergraduate teaching, to strengthen understanding of health promotion and to help shape student's attitude towards using these competencies in future dentistry practice.